Effectiveness of appropriate technology training to increase the creative economic potential of women farmers group in Cot Masam Village, Kuta Baro Sub-District, Aceh Besar [Efektivitas pelatihan teknologi tepat guna untuk peningkatan potensi ekonomi kreatif kelompok wanita tani Gampong Cot Masam Kecamatan Kuta Baro Aceh Besar] - Muyassir, M; Jufri, Yadi; Manfarizah, M; Fikrinda, F; Arabia, Teti; Lubis, Retno Leodita (Buletin Pengabdian, 2025)
Inadequate agricultural waste management can result in environmental issues such as soil and water pollution. Conversely, organic waste holds significant potential for conversion into economically valuable products like compost, enhancing soil fertility and reducing farmers' reliance on chemical fertilizers. This initiative aims to enhance the skills and knowledge of the Women Farmers Group Ingin Maju in Cot Masam Village, Kuta Baro Sub-District, Aceh Besar District, through tailored technological training. The training focuses on compost production and local microorganisms to enable the productive and sustainable utilization of organic waste, fostering entrepreneurial development in the creative economy sector rooted in organic farming. Training methodologies encompass lectures, discussions, and practical exercises involving 40 members of the women farmers group. Results indicate a substantial enhancement in participants' comprehension, particularly in compost production, with a knowledge understanding effectiveness (KUE) of 90.95% and 62.3% for LMO. Training effectiveness (TE) also reflects positive outcomes, showing a 47.6% increase for compost and 45.3% for LMO. Despite compost training being deemed more effective, the LMO training also yields favorable impacts, albeit necessitating refinements to align outcomes with compost training. Overall, this engagement successfully elevates the capacities of KWT in organic waste utilization, potentially catalyzing community-based creative economic development in this village.